Cellular cardiomyoplasty: state of the art and results of our investigation - V. A. Markov; V. V. Ryabov; T. Ye. Suslova; Yu. S. Poponina; S. V. Popov; R. S. Karpov (Бюллетень сибирской медицины)
A modern representations and opportunities of cellular technologies in cardiology and cardio surgery are summarized in article. Results of the clinical researches concerning an opportunity of participation stem cells in regeneration of a myocardium are summarized and analyzed. Results of own clinical researches devoted to studying of bearableness, safety and efficiency of different ways of delivery autologous mononuclear bone marrow cells to the damaged myocardium in patient with acute myocardial infarction are submitted.